Measurement and Estimation of Network QoS among Peer Xbox 360 Game Players - Lee, Youngki; Agarwal, Sharad; Butcher, Chris; Padhye, Jitu (PAM, 2008)
We study the quality of network connections among Xbox 360 game consoles playing Halo 3. Our data covers almost 40 million game sessions, played between over 5.6 million unique IP addresses distributed across the world, over 50 days. This paper focuses on network delay and capacity measured between Xbox 360 consoles prior to each Internet game match-up. These measurements are from packet pair probes built into the Xbox 360 networking stack. We also study the general characteristics of the player population such as geographical diversity and diurnal patterns of game play. Our study has two objectives. First, we want to better understand the characteristics of the player population. Second, we want to leverage our understanding of these characteristics to suggest ways to improve the game's matchmaking process.